Environmental action plan for a hospital - Setiawan Wangsaatmaja; Visvanathan, C.; Samorn Muttamara; Sompol Boonthanon; Her Majesty Queen Sirikit, Thailand (Bangkok : Asian Institute of Technology, 1997)
This study was conducted in the Queen Sirikit National Institute of Child Health, often called Children's Hospital in Bangkok. This hospital is a general medical hospital with 538 beds and offers treatment up to 18 years of age patients. Currently this hospital is facing problems in terms of high water consumption. The daily average water consumption of 1,034 m 3 /d consisted of hospital use (1,589 L/bed/d) and dormitory purposes (517 L/head/d). The water consumption in this hospital is 2 to 3 times higher than the other reported findings and the percentage of wastewater to water supply was 63 percent. As partly the waste audit program, possible water wastage reduction options were identified in hospital dormitories. It was discovered that about 70 m 3 /d or 7 percent of total water consumption were used inefficiently due to bad housekeeping. As a result, this hospital has been losing 263,000 Baht per year. In view of chemical or toxic wastes generated, it has been found that this hospital generated around 57 mL/bed/d. It was noted that approximately 37 percent of total chemical wastes discharged to sewers was contributed by laundry section which led to be the largest generator of chemical wastes. Air pollution, in terms of total dust, was collected in three sections of this hospital. It was found that there was no significant amount of dust concentration compared with the Thai standard. On the other hand, noise pollution for both indoor (62 dBA) and outdoor (75 dBA) of the hospital were higher than the other reported studies (30-45 dBA). At present, a 'Green Team' has been set up in this hospital which deals with the general hospital environmental improvement. In this connection, an Environmental Action Plan (EAP) was developed in this study with respect to three objectives; water wastage reduction, chemical/toxic wastes minimization and provide safe and pleasant working environment.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1997
Keywords: Hospitals -- Waste disposal; Hospitals -- Environmental services